Academic Senate Minutes 2006-04-06 - Academic Senate:::::::::
Agenda amended and approved. Minutes of 3/9/06 approved. Special Guest Trustee George Gowgani. Resolution on Workload from Art History first reading. Student Suffrage discussion. Strategic Priorities Resolution first reading. Provost Report. Vice President of Administration and Finance report. Associated Students Report.